ePortfolios as evidence of standards and outcomes in work-integrated learning - Ferns, Sonia; Comfort, J. (Asia-Pacific Journal of Cooperative Education, 2014)
Electronic portfolios (ePortfolios) are a student focused tool which support and evidence work-integrated learning (WIL) experiences and capabilities in a tertiary education setting. Such settings are increasingly faced by a regulatory framework requiring evidence of student competency and skill acquisition. The commitment of educational institutions to integrate WIL in programs of study has driven the development of electronic portfolios using various platforms. This paper will discuss how the ePortfolio has evolved in response to the WIL agenda and its potential to capture authentic assessment and evidence competencies far beyond the traditional academic transcript. The value of an electronic repository of artefacts for students in the transition from institution to employment is highlighted, and the potential benefits of employers' involvement in the future direction of ePortfolios are discussed. A case study approach is employed to articulate the possibilities and challenges of achieving institutional acceptance, support and implementation of ePortfolios.